Effects of a mobile app-based biofeedback breathing exercise program on handgrip strength, respiratory muscle activity, and pulmonary function in healthy adults - Kang, Tae-Woo; Park, Seo-Yoon; Jo, Hee-Jin (Frontiers in Rehabilitation Sciences, 2025)
IntroductionThis study investigated the effects of a mobile app–based biofeedback breathing exercise program on handgrip strength, respiratory muscle activity, and pulmonary function in healthy young adults.MethodsForty-eight participants were randomly assigned to an experimental group (n = 22), which performed app-based biofeedback breathing exercises, or a control group (n = 26), which performed traditional breathing exercises. Both groups completed three to four sessions per week for four weeks. Handgrip strength, respiratory muscle activity measured using surface electromyography, and pulmonary function assessed by spirometry were evaluated before and after the intervention.ResultsThe experimental group showed a significant within-group improvement in handgrip strength (p < 0.05), although between-group differences were not significant. Significant reductions in external intercostal and rectus abdominis activity were observed in the experimental group (p < 0.05), whereas the control group demonstrated reduced external oblique activity (p < 0.05). Both groups improved in forced expiratory volume in one second (FEV₁) and in the FEV₁/forced vital capacity (FVC) ratio (p < 0.05), with a greater improvement in FEV₁/FVC observed in the experimental group.DiscussionThese findings suggest that mobile app–based biofeedback breathing exercises may enhance respiratory efficiency and optimize muscle activation patterns in healthy young adults, supporting their potential use as an accessible adjunct tool in pulmonary rehabilitation.